(E)-Methyl-Isoeugenol as a Natural Dienophile for the Povarov Reaction Conducting to the Alkaloid-Like 2,4-Diaryl-Tetrahydroquinolines Formation - Kouznetsov, Vladimir V. (Novel Aspects on Chemistry and Biochemistry Vol. 2, 2023)
Being key structural units for various natural products and privileged scaffolds in medicinal chemistry, functionalized (tetrahydro) quinoline molecules, especially 2,4-diaryl (tetrahydro)quinoline derivatives reveal a wide spectrum of potent, interesting pharmacological activities, and unique physicochemical properties. Their synthetic method is based on the three-component Povarov reaction, in which commercially available substituted anilines and benzaldehydes are involved. The third component, trans (E)-methyl-isoeugenol, an activated dienophile, comes from the essential oil of P. pseudocaryophyllus- (E)-methyl-isoeugenol chemotype- plant, or from eugenol, another phenolic metabolite of the clove oils. In this chapter, we discuss the synthesis of some 4-(3,4-dimethoxyphenyl)-3-methyl-2-phenyl-1,2,3,4-tetrahydroquinolines that have been prepared through the Povarov reaction, and their transformations (N-furoylation reaction and oxidative dehydrogenation aromatization reaction) which led to the formation of new (tetrahydro)quinoline derivatives with alkaloid structure. Intermediate and final products interesting biological models for pharmacological agent research, especially regarding anticancer and antibacterial or antifungal drug design.